Policy networks in refugee education. (2022) - Zakharia, Zeena; Menashy, Francine; Shields, Robin
Highlights: Social network analysis of 440 organisations engaged in Syria refugee education in Lebanon. Partnerships found to comprise a complex policy web of global, national, and local actors. Policy network reflects inequities wherein international organisations hold most influence. Multiple crises impact refugee policy networks which expand to include new private actors. While COVID-19 is thought to accelerate localisation, global power hierarchies persist. Abstract: This paper presents a social network analysis of partnerships in refugee education and shows how relationships between organisations change in response to multiple crises, including political and economic crises, disaster, and COVID-19. We draw insights from an original database of 440 state and nonstate entities engaged in Syria refugee education in Lebanon (2018–2021). We find that partnerships in refugee education comprise a complex web of global, national, and local actors. The policy network arising from these partnerships reflects power inequities wherein international organisations hold most influence. Moreover, crises impact the network, which expands to include new private actors. While the COVID-19 pandemic is thought to accelerate localisation, our analysis suggests the durability of global power hierarchies in refugee education response.